Revitalizing the International Law Discourse on the Prohibition of Maritime Piracy: Voices from International Law Commission’s Work on Peremptory Norms of General International Law (Jus Cogens) - Alexander, Atul (Transactions on Maritime Science, 2024)
The International Law Commission (ILC) is tasked with the codification and progressive development of international law. Recently, the ILC submitted to the United Nations General Assembly (UNGA) in its 73rd session ‘Draft Conclusions on identification and legal consequences of peremptory norms of general international law (jus cogens)’. The report holds significance as the concept of the jus cogens has been shrouded in mystery since its inception in the Vienna Convention on the Law of Treaties (VCLT) in 1969. The Draft Conclusion 23 (non-exhaustive list) identifies eight norms (annex) fulfilling the requirement of jus cogens. The ILC clearly states that “…the inclusion of the list in the annex in no way precludes the existence of other norms that may have a peremptory character or the emergence of other norms in the future having that character.”[1] Thus leaving space for the inclusion of fresh norms through subsequent studies. Nonetheless, the ILC provided the techniques to identify peremptory norms under Draft Conclusions 4 to 9. Through this article, the author argues that the prohibition of piracy has matured into a jus cogens norm. This is done by applying the techniques formulated by the ILC in its recent report. Although there are several writings on the prohibition of piracy as customary international law, it has received scant attention in the context of the jus cogens, and the author intends to fill this lacuna. This study assumes relevance as States increasingly adopt domestic legislation to combat piracy.